Development of a science process skills-based interactive website ‘bioenial’ on environmental pollution material - Rahmawati, Atika Budi; Bowo, Sugiharto; Santosa, Slamet (Biosfer: Jurnal Pendidikan Biologi, 2022)
This study aims to develop an interactive website based on the science process skill ‘Bioenial’ on Environmental Pollution material for grade X SMA/MA and identify the achievement of science process skills in the use of the 'Bioenial' website. This study was designed based on the Research & Development design from the Thiagarajan 4D development model (Define, Design, Develop and Disseminate). The instruments used in this study were media and material expert validation sheets, student worksheets, and student and teacher response sheets. The analysis technique used the Rasch analysis. The results showed that (1) the Feasibility of the 'Bioenial' website, the average percentage score of validity obtained from the three media experts was 97,4% that within the "Very Eligible" category, and the percentage score from the material experts was 76.6% or within the "Eligible" category. The 'Bioenial' website was tested in a class of 32 students and on two biology teachers. The results of student responses according to the person measure obtained a mean of 85.5, meaning that the website is "Eligible" to use. The results of the teacher's response show that the Bioenial website is "Appropriate" for learning. (2) Science process skills can be developed on environmental pollution materials with the 'Bioenial' website observing, classifying, predicting, communicating, designing, and conducting experiments. Assessment of the skills of conducting experiments is unlikely during the distance learning period due to the difficulty to provide evaluations. Based on the study results, further research is needed to determine the effectiveness of the 'Bioenial' website in improving students' cognitive learning outcomes.